2011
DOI: 10.2174/138920111798280956
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Endogenous H2S in Cardiovascular Physiology

Abstract: Recent research has shown that the endogenous gas hydrogen sulphide (H2S) is a signalling molecule of considerable biological potential and has been suggested to be involved in a vast number of physiological processes. In the vascular system, H2S is synthesized from cysteine by cystathionine-γ-lyase (CSE) in smooth muscle cells (SMC) and 3- mercaptopyruvate sulfuresterase (3MST) and CSE in the endothelial cells. In pulmonary and systemic arteries, H2S induces relaxation and/or contraction dependent on the conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(47 citation statements)
references
References 0 publications
1
41
0
5
Order By: Relevance
“…Previous reports showed that glycerophosphatidylcholine concentration typically increases with age; moreover, this increase is more pronounced in aged AD patients and those with enhanced A ␤ plaque formation (29)(30)(31)(32). Breakdown of APP and aggregation of amyloid plaques are the major causes of neuronal deterioration in AD.…”
Section: Discussionmentioning
confidence: 97%
“…Previous reports showed that glycerophosphatidylcholine concentration typically increases with age; moreover, this increase is more pronounced in aged AD patients and those with enhanced A ␤ plaque formation (29)(30)(31)(32). Breakdown of APP and aggregation of amyloid plaques are the major causes of neuronal deterioration in AD.…”
Section: Discussionmentioning
confidence: 97%
“…This factor is a potentially important modulator in the regulation of organ blood flow and vascular resistance during normal physiological states in animal (3,4) and in the human circulation (5 -8) and plays an even greater release of EDHF and NO from the endothelium (20) and is defined as the third kind of novel gaseous transmitter besides NO and carbon monoxide (20). It has been shown that vascular endothelium can induce production of endogenous H 2 S, leading to hyperpolarization and vasorelaxation responses (21) and that H 2 S is involved in regulating a vast number of physiological and pathological processes in vitro (22,23).…”
Section: Introductionmentioning
confidence: 99%
“…13,14) Hydrogen sulfide (H 2 S), a newly characterized gasotransmitter, has recently been shown to have cardioprotective effects. 15,16) Endogenous H 2 S is synthesized in the mammalian body from L-cysteine by the activity of three enzymes, cystathionine-γ-lyase (CSE), cystathionine-β-synthetase (CBS), and 3-mercaptopyruvate sulfurtransferase (3-MST). 17) In myocardium, H 2 S is generated predominantly by CSE.…”
mentioning
confidence: 99%